Peran Pendidikan Islam dalam Membentuk Generasi Islami - Adin, Ahmad Muchlis; Fauzi, Sriyono (TSAQOFAH, 2024)
Education is a perfect process that organizes, educates and nurtures a generation so that it has the ability to process data so that it becomes something useful. Islamic education is an important factor in life. With Islamic education, a person will be guided towards noble morals and character in accordance with the guidance of the Al-Quran and Sunnah. Creating an ethical, moral society and preparing ourselves to face the challenges of trials in this world and the hereafter. Islamic education has a noble goal, namely that a person has faith, piety, knowledge and noble character.